FACTORS OF FISH CONDITION Glossogobius matanensis AS AN EFFORT TO DOMESTICATE ENDEMIC FISH IN LAKE TOWUTI - Bobi Bobi; Nursyahran Nursyahran; Heriansah Heriansah; Arnold Kabangnga (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
Glossogobius matanensis is one of the endemic fish species found only in Lake Towuti, South Sulawesi. Its limited population and environmental pressures make it necessary to conserve efforts through a domestication approach. This study aims to analyze the condition factor of G. matanensis fish as an indicator of health and biological readiness in the context of domestication. Sampling was carried out at several points in the waters of Lake Towuti using the purposive sampling method. The observed parameters included total length, body weight, and condition factor (K) which were calculated using the King formula. The results showed that the value of the condition factor ranged from 1.00–1.05 which indicated that the fish was in good physiological condition. The variation in K-values also reflects differences in habitat quality and availability of natural feed in each location. These findings provide an important basis for the development of early aquaculture technologies and support long-term conservation programs for this endemic species. The domestication of G. matanensis is seen as an adaptive strategy to maintain the sustainability of local genetic resources amid changes in the ecosystem of Lake Towuti